2013
DOI: 10.1177/193229681300700611
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Partial Pressure of Oxygen in Blood Samples on Measurement Performance in Glucose-Oxidase-Based Systems for Self-Monitoring of Blood Glucose

Abstract: These data suggest that capillary blood pO2 variations lead to clinically relevant BG measurement deviations in GOx systems, even in GOx systems that are not labeled as being oxygen sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
14
1
2
Order By: Relevance
“…On the other hand, low oxygen levels (eg, in patients with severe chronic obstructive pulmonary disease) might help deliver falsely high BG values. 23,56 On the other hand, a study using GD test strips showed them not to be significantly affected by different oxygen pressure. 54 With a GO-based measurement, however, an increase in pO 2 to >100 Torr (eg, in critically ill patients receiving oxygen treatment) may result in a remarkable underestimation of BG values.…”
Section: Physiological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, low oxygen levels (eg, in patients with severe chronic obstructive pulmonary disease) might help deliver falsely high BG values. 23,56 On the other hand, a study using GD test strips showed them not to be significantly affected by different oxygen pressure. 54 With a GO-based measurement, however, an increase in pO 2 to >100 Torr (eg, in critically ill patients receiving oxygen treatment) may result in a remarkable underestimation of BG values.…”
Section: Physiological Factorsmentioning
confidence: 99%
“…22,54 An evaluation of 5 SMBG systems utilizing a GO enzyme reaction on test strips showed BG measurements to be affected by pO 2 values < 45 and ≥ 150 mmHg in the blood sample. 56 The practical relevance of these correlations is highlighted by an investigation of capillary blood samples obtained from the fingertips of 110 patients (31 with type 1 diabetes mellitus, 69 with type 2 diabetes, 10 without diabetes, no acute serious diseases). A broad range of capillary pO 2 values was demonstrated to occur in daily clinical practice.…”
Section: Physiological Factorsmentioning
confidence: 99%
“…It has been argued that the lower reported glucose levels observed at higher altitudes are the result of methodological artifacts. There is strong evidence demonstrating the inconsistency of the performance of portable blood glucose meters in the presence of low oxygen tension (47)(48)(49)(50)(51) and low ambient temperatures (47)(48)(49)(50)(51). In addition, an increased number of red blood cells caused by high altitudes may also have affected glucose readings in blood glucose meters, due to mechanical impairment of the diffusion of plasma into the reagent membrane (52).…”
Section: Glucosementioning
confidence: 99%
“…Causes of falsely high BGM values include: low hematocrit (<35%), hyperuricemia, low partial pressure of oxygen (<45mm Hg) in GO based devices, and acetaminophen. Factors that falsely decrease BGM values include: elevated hematocrit (>45%), hypertriglyceridemia, decreased tissue perfusion at the testing site, elevated partial pressure of oxygen (>150mm Hg) in GO-based devices, and ascorbic acid (18)(19)(20)(21)(22)(23)(24). High maltose levels in peritoneal dialysis solution, intravenous immunoglobulin G, Rho (D) immunoglobulin, Abatacept, and tositumomab cause falsely high BG concentrations with glucose meters that use GDH-PQQ (25).…”
Section: Inaccuracies In Bgmmentioning
confidence: 99%